The Effect of Demand Response in the Minimum Available Reserve of Energy Management - Soares, João (2016)
This paper presents a multi-objective energy scheduling for the daily operation of a Smart Grid (SG) considering maximization of the minimum available reserve in addition to the cost minimization, to take into account the reliability requirements of critical and vulnerable loads. A Virtual Power Player (VPP) manages the day-ahead energy resource scheduling in the smart grid, considering Distributed Generation (DG) and Vehicle-To-Grid (V2G), while maintaining a highly reliable power for the critical loads. This work considers high penetration of critical loads, e.g. industrial processes that require high power quality, high reliability and few interruptions. A mathematical formulation is described and a deterministic technique based on Mixed-Integer Linear Programming (MILP) is used to solve the multi-objective problem. The effect of some customers with DR in this context is analyzed to assess the benefits in the energy scheduling problem. A case study using a 180-bus Portuguese distribution network with 90 load points, several DG units and a large fleet of Electric Vehicles (EVs) with V2G is used to illustrate the performance of the proposed method.